Іnstitute criminal offenses in the context of criminal justice reform modern Ukraine - Яремко, О. М.; Ониськів, І. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article examines compliance institute criminal offenses necessarily legal humanism as the basis forreforming criminal justice in modern Ukraine. The authors concluded that in the present Ukrainian introductionof criminal offenses is premature, as no for the theoretical and legal basis, without any intention of humanizationcan result in repressive and punitive criminal justice system.